Oxygen saturation targets in infants with bronchiolitis (BIDS): a double-blind, randomised, equivalence trial. Issue 9998 (12th September 2015) - Cunningham, Steve; Rodriguez, Aryelly; Adams, Tim; Boyd, Kathleen A; Butcher, Isabella; Enderby, Beth; MacLean, Morag; McCormick, Jonathan; Paton, James Y; Wee, Fiona; Thomas, Huw; Riding, Kay; et al.
Summary: Background: The American Academy of Pediatrics recommends a permissive hypoxaemic target for an oxygen saturation of 90% for children with bronchiolitis, which is consistent with the WHO recommendations for targets in children with lower respiratory tract infections. No evidence exists to support this threshold. We aimed to assess whether the 90% or higher target for management of oxygen supplementation was equivalent to a normoxic 94% or higher target for infants admitted to hospital with viral bronchiolitis. Methods: We did a parallel-group, randomised, controlled, equivalence trial of infants aged 6 weeks to 12 months of age with physician-diagnosed bronchiolitis newly admitted into eight paediatric hospital units in the UK (the Bronchiolitis of Infancy Discharge Study [BIDS]). A central computer randomly allocated (1:1) infants, in varying length blocks of four and six and without stratification, to be clipped to standard oximeters (patients treated with oxygen if pulse oxygen saturation [SpO2 ] <94%) or modified oximeters (displayed a measured value of 90% as 94%, therefore oxygen not given until SpO2 <90%). All parents, clinical staff, and outcome assessors were masked to allocation. The primary outcome was time to resolution of cough (prespecified equivalence limits of plus or minus 2 days) in the intention-to-treat population. This trial is registered with ISRCTN, number ISRCTN28405428. Findings: Between Oct 3, and March 30, 2012, and Oct 1, and March 29, 2013, we randomly assigned 308 infants to standard oximeters and 307 infants to modified oximeters. Cough resolved by 15·0 days (median) in both groups (95% CI for difference −1 to 2) and so oxygen thresholds were equivalent. We recorded 35 serious adverse events in 32 infants in the standard care group and 25 serious adverse events in 24 infants in the modified care group. In the standard care group, eight infants transferred to a high-dependency unit, 23 were readmitted, and one had a prolonged hospital stay. In the modified care group, 12 infants were transferred to a high-dependency unit and 12 were readmitted to hospital. Recorded adverse events did not differ significantly. Interpretation: Management of infants with bronchiolitis to an oxygen saturation target of 90% or higher is as safe and clinically effective as one of 94% or higher. Future research should assess the benefits and risks of different oxygen saturation targets in acute respiratory infection in older children, particularly in developing nations where resources are scarce. Funding: National Institute for Health Research, Health Technology Assessment programme.